Literasi Keuangan, Teknologi Sistem Informasi, Pengendalian Intern dan Kualitas Laporan Keuangan UMKM - Sularsih, Hermi; Wibisono, Sukarno Himawan (E-Jurnal Akuntansi, 2021)
The purpose of this research is to explain how financial literacy, information system technology, and internal control on the quality of financial reports in the era of the industrial revolution. The study used a descriptive quantitative method of 437 MSME in Pasuruan Regency and multiple regression analysis with primary data and purposive sampling as the method of selecting samples. The results of this research indicate that financial literacy (X 1 ), information system technology (X 2 ), have an effect on the quality of MSME financial reports in the revolutionary era 4.0, while internal control (X 3 ) has an effect but is not significant on the quality of MSME financial reports in the revolutionary era 4.0. Keywords: Financial Literacy; Information Systems Technology; Internal Controls; Quality.